PERILAKU SUPPORTER SEPAKBOLA PSIM YOGYAKARTA - Fradiantika, Vita (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2014)
This study aims to investigate the behavior of PSIM’s (Perserikatan Sepakbola Indonesia Mataram) supporters. This study used qualitative methods with case study approach. Informants used in this study consist of three members of Brajamusti board and three members of the Maident board. For the triangulation, in this study the Brajamusti President, Chairman of The Maident, and two police officers were interviewed. The results showed that Brajamusti and The Maident are behave fanatic in providing support to PSIM, so that often cause fights between supporters. Factor that cause the broken of Brajamusti is political that made by certain parties for political interests. The positive impact of these two groups of supporters are their contribution for buying tickets in every time they watch PSIM, so it can be a financial support. While the negative impact of the two groups of supporters are the unfair competition between them that makes support for PSIM become obscured